Bioremediation of a Chromium Complex Dye Using Aspergillus flavus and Aspergillus tamarii. Issue 9 (15th August 2016) - Ghosh, Arpita; Dastidar, Manisha Ghosh; Sreekrishnan, Trichur Ramaswamy
Abstract: Bioremediation of a chromium complex dye was conducted by growing Aspergillus flavus and Aspergillus tamarii in a batch bioreactor to evaluate color and chromium removal. A. tamarii was found to be more efficient for bioremediation of this dye in the initial concentration range. The optimum conditions of parameters for color removal were determined using response surface methodology. The theoretical and experimental responses of color removal were in close agreement as suggested by the confirmatory experiments performed in batch and continuous modes under the optimum conditions. The bioremediation mechanism of the chromium complex dye was examined by gas chromatography‐mass spectrometry, scanning electron microscopy, transmission electron microscopy, and energy‐dispersive X‐ray spectroscopic analyses. Abstract : Bioremediation is an environmentally friendly and cost‐effective process for removal of contaminants from industrial wastewater, but to date only little work has been reported considering removal of metal complex dyes. Bioremediation of a chromium complex dye was successfully performed by two strains of Aspergillus sp. in a batch bioreactor to evaluate color and chromium removal.